Increased Yield of Human Tissue-Type Plasminogen Activator Obtained by Means of Recombinant DNA Technology - Browne, M J; Dodd, I; Carey, J E; Chapman, C G; Robinson, J H (Thrombosis and Haemostasis, 1985)
Extra copies of the human tissue-type plasminogen activator (t-PA) gene were introduced into the Bowes melanoma cell line. We obtained a recombinant cell line (TRBM6) which secretes approximately ten-fold more t-PA than the parent cell line. The identity of the plasminogen activator made by the new cell line was confirmed by sizing on sodium dodecyl sulphate polyacrylamide gels and by specific quenching using anti-t-PA antibody. We estimate that the recombinant line produces t-PA at a rate of approximately 3 pg/cell/24 hr and that t-PA accumulates in the harvest medium at a rate of approximately 4000 International t-PA Units/ml/24 hr.
Keywords: Tissue-type plasminogen activator; Fibrinolysis; Recombinant DNA